Complexo Nova Venécia e magmatismo associado, Orógeno Araçuaí, estado do Espírito Santo - Camila Tavares Gradim (2013)
A hard challenge in Precambrian regions can be to decode tectonic environments and related processes from basin fill to orogenic stages, particularly in high metamorphic grade terrains. The backarc region of the Araçuaí orogen, located to the east of the Rio Doce calc-alkaline magmatic arc (630 585 Ma), provides excellent outcrops for such studies as it shows a huge amount of wellpreserved Al-rich gneisses and related granites. Accordingly, here we present robust datasets ofisotopic (UPb and SmNd) and lithochemical results from those rocks. Regionally, the most fertile sources of granitic melts are the Nova Venécia paragneisses (Qtz + Pl + Kfs + Bt + Grd ± Crd ± Sil ± Hc ± Opx ± melt) that reached metamorphic peak PT conditions at 800900 °C and 58 kbar. Our data suggest a maximum depositional age around 590 Ma for the graywacky protoliths of the Nova Venécia paragneisses, with main sediment sources located in continental active margin settings. Partial melting processes started on backarc deposits yet during the late development of the Rio Doce arc, around 590585 Ma, forming autochthonous peraluminous melts (the G2 Ataléia Suite) closely associated to the Nova Venécia paragneisses. Progressive anatexis and melt accumulation attained a climax at 575560 Ma, forming the collisional Carlos Chagas batholith, a gigantic mass of garnetbiotite granite crowded with Kfeldspar megacrysts. The general crustalsuccession shows a zone rich in (Opx±Hc±Pl)-Sil-Crd-Kfs granulite, at the base, followed by migmatitic paragneisses gradually richer in Ataléia melts, underlying the Carlos Chagas batholith. To the south of this batholith, Opxbearing rocks are widespread and melt accumulation zones are relatively small. Around 545530 Ma, another anatectic episode formed Crd±Grd leucogranites (G3), mostly from the remelting of the collisional (G2) Ataléia and Carlos Chagas granites. Finally, an important postcollisional, Itype plutonism took place around 520490 Ma, imposing a regional reheating that formed large high-grade thermal aureoles. This long lasting (c. 100 m.y.) history of granite generation required distinct heat sources, such as asthenosphere ascent under thebackarc region in the precollisonal stage, thrust stacking of the hot arc onto the backarc, radiogenic heat release from the collisional thickened crust and, finally, asthenosphere uprising following mantle delamination during the gravitational collapse of the Araçuaí orogen.